2014
DOI: 10.1007/s40279-014-0150-5
|View full text |Cite
|
Sign up to set email alerts
|

Exercise, Nutrition and the Brain

Abstract: Accumulating evidence suggests that diet and lifestyle can play an important role in delaying the onset or halting the progression of age-related health disorders and can improve cognitive function. Exercise has been promoted as a possible prevention for neurodegenerative diseases. Exercise will have a positive influence on cognition and it increases the brain-derived neurotrophic factor, an essential neurotrophin. Several dietary components have been identified as having effects on cognitive abilities. In par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
140
1
23

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(166 citation statements)
references
References 81 publications
2
140
1
23
Order By: Relevance
“…There is a small but growing body of research on the cognitive and mood consequences of chocolate and cocoa consumption [17,[20][21][22][23]; however, there appear to be only a few studies concerning the influence of the consumption of cocoa flavanols per se on acute changes in cognitive performance or mood. One experiment found that, compared to white chocolate containing trace amounts of flavanols, the consumption of dark chocolate containing 773 milligrams (mg) of cocoa flavanols improved spatial memory and reaction time during the predictable phase of an attention task performed 2 to 2.75 h (hrs) post-consumption [24].…”
Section: Introductionmentioning
confidence: 99%
“…There is a small but growing body of research on the cognitive and mood consequences of chocolate and cocoa consumption [17,[20][21][22][23]; however, there appear to be only a few studies concerning the influence of the consumption of cocoa flavanols per se on acute changes in cognitive performance or mood. One experiment found that, compared to white chocolate containing trace amounts of flavanols, the consumption of dark chocolate containing 773 milligrams (mg) of cocoa flavanols improved spatial memory and reaction time during the predictable phase of an attention task performed 2 to 2.75 h (hrs) post-consumption [24].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is also an important factor that can be responsible for a decline in cognitive function [3]. Therefore, exercise and nutrition are both powerful means that influence brain structure and function [5]. Diet and regular exercise are two non-invasive approaches that can be used to enhance neural signaling by influencing synaptic transmission, brain plasticity, and cognitive function [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…BDNF; glukoz oksidasyonunu artırmakta, kan glukoz düzeyini düşürmekte ve insülin hassasiyetini artırmaktadır. 39 Yani enerji metabolizması ve homeostazda denge sağlayarak, leptin hassasiyetini artırır. Leptinin etkisi ise iştahı azaltmak ve enerji harcamasını artırmaktır.…”
Section: Egzersi̇zi̇n İnflamatuar Ve Metaboli̇k Yanitlara Etki̇si̇unclassified
“…Yedi alt gruba sahip polifenollerin en önemli grubu flavonoid içeren gıdalardır. 39 Beslenmede, bu gıdaların temel alınması durumunda CREB ve LTP aktivasyonuna katkı sağladıkları için beyin fonksiyonlarında iyileştirici etkileri olabileceği bildirilmektedir. 39 Egzersizin yanı sıra, beyin fonksiyonlarını iyileştirici ileriye dönük stratejiler arasında progesteron, statinler, siklosporin-A vb.…”
Section: Beslenme Ve Farmakoloji̇k öNeri̇lerunclassified